A qualitative exploration of NHS-staff social identification with mindfulness in-groups and engagement with mindful practices - Daniel Cullen; Kate Cavanagh; Clara Strauss (PLoS ONE, 2025)
Background/ objectives Mindfulness practice has been widely adopted by healthcare staff, being grounded in evidence and supported by national guidelines. However, certain fundamental factors are not well understood, including attitudes towards mindfulness in-groups. The aim of this project was to explore the nature of social identification with mindfulness in-groups in relation to engagement with mindful practices. Methods Twenty healthcare staff from three healthcare Trusts were recruited to engage in semi-structured interviews of one-hour duration. Transcripts of these interviews were then subjected to reflexive thematic analysis. Results Social identification was simultaneously rich and fluid, with some tentative evidence of positive boosts to psychological engagement tempered by dissonance about current physical engagement levels. Healthcare and mindfulness identities complemented, in that being aided doing, aligning values and aspirations, although clashes also presented through culture, depending on one’s sense of connection/disconnection. Discussion/ conclusions Employers and trainers could consider implementing strategies to enhance social identification with mindfulness in-groups. Further research should also explore whether strength of social identification translates into improved engagement with mindful practices.